Implantação de práticas de inspeção contínua: um estudo de caso na disciplina de manutenção de software - Lima, Antônia Naelly Freire de (2024)
Continuous inspection to ensure the delivery of quality software is an essential practice that should be incorporated and mastered by students in the software development field. However, research indicates that the teaching and learning of these techniques face significant challenges and are often underestimated in most higher education institutions. In the workforce, continuous inspection has become a fundamental practice in software development, contributing to the impro vement of the final product’s quality and efficiency. This research focused on the implementation of the continuous inspection tool, Sonar Cloud, during a source code refactoring project. The experiment was conducted in a classroom setting with students from the Software Maintenance course at the Federal University of Ceará - Campus Russas, in the 2023.2 semester. The aim was to assess how the introduction of continuous inspection affects the maintenance process of students’ projects, helping them minimize the impact of changes and avoid introducing new problems into the software. The results demonstrated that the adoption of continuous inspection, through Sonar Cloud, significantly helped students identify poor coding habits, detect existing bugs in the code, and prevent new errors during the refactoring of their projects. Moreover, they showed that teamwork was highly valued by the students, who recognized the importance of inspection practices in ensuring the delivery of high-quality software. This research highlights the importance of integrating techniques and tools widely used in the industry into the academic environment, promoting a learning experience more aligned with professional practices and better preparing students for the challenges of the software industry.